2015
DOI: 10.1007/s11897-015-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Risk and Preventing 30-Day Readmissions in Decompensated Heart Failure: Opportunity to Intervene?

Abstract: Heart failure (HF) patients are at high risk of hospital readmission, which contributes to substantial health care costs. There is great interest in strategies to reduce rehospitalization for HF. However, many readmissions occur within 30 days of initial hospital discharge, presenting a challenge for interventions to be instituted in a short time frame. Potential strategies to reduce readmissions for HF can be classified into three different forms. First, patients who are at high risk of readmission can be ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 76 publications
(77 reference statements)
0
27
0
Order By: Relevance
“…10 Potential systems-level solutions include care by nurse practitioners, physician assistants and transitional care clinics. 45 Telemedicine is an option of increasing interest for follow-up of patients in remote areas. Health insurance is one of the most important predictors of obtaining follow-up care; 46,47 therefore, in the US, outcomes will likely be affected by the future of the Affordable Care Act.…”
Section: Discussionmentioning
confidence: 99%
“…10 Potential systems-level solutions include care by nurse practitioners, physician assistants and transitional care clinics. 45 Telemedicine is an option of increasing interest for follow-up of patients in remote areas. Health insurance is one of the most important predictors of obtaining follow-up care; 46,47 therefore, in the US, outcomes will likely be affected by the future of the Affordable Care Act.…”
Section: Discussionmentioning
confidence: 99%
“…Development and effective implementation of such strategies requires tools that can accurately identify low‐risk patients that can be safely discharged and treated less aggressively post‐discharge and high‐risk patients for whom more intensive in‐hospital and post‐discharge management is justified. Nevertheless, prediction of post‐discharge events, particularly readmissions, with readily available clinical variables and standard laboratory parameters remains challenging . Biomarkers can play an essential role in improving objective pre‐discharge risk stratification and several promising prognostic biomarkers are currently available in AHF thanks to significant advances in proteomic research over recent years .…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been proposed to reduce the enormous burden of early post‐discharge events on patients and health care systems . Several observational data suggested that longer hospital stay and intensified post‐discharge care are among the strategies that can be potentially beneficial in terms of lowering 30‐day readmission rates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey done in Iran found that 25% of patients hospitalized in heart wards are suffering from heart failure (4). Elderly patients with heart failure are also at increased risk for early hospitalization, with rates of readmission ranging from 29 to 47% within three to six months of the initial discharge (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%